2007
DOI: 10.2174/157016107779317206
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Endothelium-Derived Hyperpolarizing Factor in the Human Circulation

Abstract: Although nitric oxide (NO) is recognized as the primary vasodilator derived from vascular endothelium in regulating the vascular tone, another factor, i.e. the endothelium-derived hyperpolarizing factor (EDHF), has recently gained much attention and has been demonstrated to participate in vasodilatation in various blood vessels from different species, despite its unidentified nature. Most of the studies were conducted in animals and the knowledge of this factor in the human vasculature is relatively limited. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 102 publications
2
22
0
1
Order By: Relevance
“…It has been established that NO is involved predominantly in the control of vascular tone in larger conductance vessels, whereas in microcirculation, the role of EDHF seems to be more important (Pohl & deWit, 1999;Urakami-Harasawa et al, 1997). Most observations are based predominantly on animal studies and little is known about the impact of EDHF in humans in vivo (Yang et al, 2007). In spite of several investigations, the exact interaction of these mechanisms is still not well defined, specially not in human skin microcirculation.…”
Section: Endothelium As a Local Regulator Of Vascular Tonementioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that NO is involved predominantly in the control of vascular tone in larger conductance vessels, whereas in microcirculation, the role of EDHF seems to be more important (Pohl & deWit, 1999;Urakami-Harasawa et al, 1997). Most observations are based predominantly on animal studies and little is known about the impact of EDHF in humans in vivo (Yang et al, 2007). In spite of several investigations, the exact interaction of these mechanisms is still not well defined, specially not in human skin microcirculation.…”
Section: Endothelium As a Local Regulator Of Vascular Tonementioning
confidence: 99%
“…The existence of endothelium-dependent, NO/PGI 2 -independent relaxations, potentially attributable to an EDHF, has been confirmed in humans in vivo. Based on studies in patients who exhibited a NO/PGI 2 -independent response to an endothelial challenge, it has been suggested that EDHF might serve as a backup vasodilator in the settings of compromised endothelial function (Fichtlscherrer et al, 2004;Fischer et al, 2007;Taddei et al, 2006;Yang, 2007). Different putative mechanisms are proposed to mediate the EDHF-mediated vasodilation:…”
Section: Human Skin Microcirculation and The Endothelium: Impact Of Nmentioning
confidence: 99%
“…We have previously reported a clear sex difference in endothelial function, where the non-nitric oxide, noncyclooxygenase products attributed to the endothelium-derived hyperpolarization (EDH)-type response, plays a greater role in females compared to males [11,12]. The EDH-type responses play a role under physiological conditions either in health or in disease [13,14]. In cardiovascular diseases, endothelial dysfunctions have been reported, where the release of NO, one of the important endothelium-derived vasodilators is compromised [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms contribute to the EDHF phenomenon and their contribution to vasodilatation varies depending on the species and vascular bed studied (Shimokawa et al 1996, Busse et al 2002, Yanga et al 2007) as well as on the agonist used to stimulate the endothelium (Taddei et al 2006, de Wit & Wolfle 2007, Lenasi 2009). Several mechanisms contribute to the EDHF phenomenon and their contribution to vasodilatation varies depending on the species and vascular bed studied (Shimokawa et al 1996, Busse et al 2002, Yanga et al 2007) as well as on the agonist used to stimulate the endothelium (Taddei et al 2006, de Wit & Wolfle 2007, Lenasi 2009).…”
mentioning
confidence: 99%